Experts in Their Own Lives: Children’s Understanding of Their Immigration Status and, Subsequently, Their Identity / Ariana Mangual Figueroa’s Knowing Silence: How Children Talk about Immigration Status in School - Gilmore, Wraychel (Journal of Childhood Studies, 2024)
By examining what transpires at school for children of mixed-status immigrant families in what is spoken and what is kept silent, Figueroa demonstrates students’ depth of understanding of their own immigration status and how it shapes their self-identity. Through this collaborative longitudinal research, citizenship and self-advocacy are explored in a manner that amplifies marginalized students’ voices and expertise.